Factors influence on housing finance customers - Thamodaran, V. (university of Jaffna, 2014)
Housing Finance is linked with the provision of infrastructure and utilities because it has a clear relationship with the volume of new stock which will be built. As mentioned earlier, housing finance plays an intermediary role between production consumption economy and housing system. Through change in polices in the capital market can be expanded so that a part of the resources flow into housing. Thus, housing finance is an important link in the potential for transforming the creation of housing and social urban investment into strips of property and benefit for the people including low income groups. How the flow of resource helps the wider range of income groups will depend upon the terms and conditions built into the design of housing credit. Generally, housing requires longer term finance than the one in industry
Keywords: Finance; Infrastructure; Utilities